THE TERRITORIAL IDENTY OF LATGALE IN THE CROSSROADS OF GLOBALIZATION AND GLOCALIZATION - Runce, Inese (Via Latgalica, 2013)
The aim of this paper is to analyze the processes of formation of Latgale’s territorial identity during the age of globalization in the last 20 years. Research was carried out using the latest data of qualitative research of the Institute of Philosophy and Sociology of University of Latvia (the thematic research of Latvian Science Council’s project "Political development of the nation's self-confi dence after restoration of Latvian independence: Trends and Factors," head of project: Inese Runce, 2009-2012) and the latest theoretical insights of territorial identity construction processes under the impact of globalization and glocalization. On the basis of analysis of the socio-political processes and the experience of other countries, it must be emphasised that the placemaking is an important political process, not only at national but also at sub-regional level. Regional authorities should be able to offer a specifi c political vision, not only to the national power authorities, but also to the main bearers of regional identity - the people in regions. As it is shown by the recent studies, during the past 20 years in Latvia, the regional identity manifests itself only in Latgale where it is alive and vibrant, and the care and preservation and making of identity comes directly from the very bearers of this identity. Regional authorities, in collaboration with local NGOs, experts on culture, etc. must also contribute to the internal integration of the region, where each municipality and each form of local identity has its own recognized place and function, creating diverse forms of sustainable regional communities and regional identities. Regional identity is not exclusive and is able to unite different religious, ethnic, linguistic groups in a single whole entity. Over the past twenty years the process of formation of Latgale regional identity can be divided into three stages: 1. 90s of 20th century – the stage of denial of regional identity. In this decade the preservation and construction of Latgale regional identity is carried out only by few individuals or interest groups: writers, researchers, artists, local intellectuals who are mainly based in the circles of local intellectuals at Rezekne University College, as well as indirectly Latgale Research Institute of Daugavpils University; 2. The fi rst decade of 2000s - a gradual increase of awareness of regional identity. During the period this has been a gradual growth of awareness of regional identity and its development process. "Latgale radio”, Latgalian music groups are being launched, also the extensive scientific and political debate on the status of Latgale language started, socio-linguistic research projects initiated and a new non-governmental organizations established, the first portals in Latgalian as well the new initiative of regional municipalities are being launched; 3. 2010 to 2013 - analyzing the last three years of political and intellectual life trends, it can be argued that a qualitatively new stage in the recognition of regional identity and its construction process has been created: current political debate before and after the elections of 11th Saeima and the language referendum, discussions on the role of Latgalian as regional language, the National Development plan (NDP), development of the structural budget plans. However, it is clear that those spring sprouts must be protected, due to the fact that the strong centralizing tendencies in the Latvian political culture still exist.